Patient Experience Management as a Tool for Internationalization in Foundation Cardiovascular of Colombia - León-Becerra, Juan; Martinez Sanchez, Jorge; Morales Adarme, Andres (Universitas Ahmad Dahlan, 2023)
Medical tourism, also known as healthcare tourism or medical travel, refers to traveling to a foreign country to receive medical treatment. Medical tourism has recently become increasingly popular, with millions traveling abroad for healthcare services yearly. However, medical tourism is not without its challenges. Patients must carefully research and select healthcare providers and facilities, considering factors such as accreditation, quality of care, and patient safety. Patients may also face cultural and language barriers when seeking treatment in a foreign country. The present work aims to establish the bases and knowledge to determine the importance of patient satisfaction as a factor of competitiveness. This work presents a study case centralized in the institutions providing health services (IPS in Spanish): Cardiovascular Foundation of Colombia (FCV) and a detailed analysis of the internationalization processes established by the Cardiovascular Foundation. For this, each of the processes was categorized and detailed in such a way that it would allow identifying which are the determining factors in the patient's experience and how to improve them. Each proposed strategy consists of a theoretical framework of the topic to be developed, objectives, approach, methodology, and development. Finally, the results obtained are the product of the analysis of surveys applied to the objective users, theoretical verifications, interviews, and work groups with directors of the Cardiovascular Foundation of Colombia.